Protocol for a Qualitative Study on Household Economic Discourses: From Everyday Talk About Money to Economic Abuse and the Financial Consequences of Intimate Partner Violence - Pernilla Liedgren; Marie Eriksson; Helena Blomberg (International Journal of Qualitative Methods)
Intimate partner violence (IPV) constitutes a global societal challenge. Interventions against IPV have been implemented worldwide. However, the problem still prevails and takes new forms. Despite conceptual developments and a growing body of knowledge on economic abuse (EA) in recent years, there remains a significant lack of qualitative research on experiences of economic abuse . The study aims to expose and examine discourse s on household economy , economic abuse, and the financial consequences of IPV from an intersectional perspective , thereby contributing to the theoretical development of the field. The project’s theoretical framework is grounded in an interactionist and constructivist perspective. We focus on symbolic and social boundaries to explore how individuals understand and position themselves in relation to others regarding the household economy and gendered economic abuse. Using discourse analysis as a method, the project focuses on conflicts in household economies, economic abuse, and the economic consequences of IPV. The study design is qualitative, exploratory, intersectional, and comparative, and it aims to develop the theoretical field of IPV and economic abuse. Sub-study one is based on narrative and discursive psychological analysis of focus group interviews with individuals between 25 and 70 years old. In sub-study two, the focus is initially on women’s narratives about experiences of economic abuse and the economic consequences of IPV that they have been subjected to. In the second part of sub-study two, a re-analysis of the collected empirical material will be conducted to discern patterns in the interviewees’ narratives about experiences of power and control in relation to economics. The project is expected to contribute knowledge for professionals. It will also contribute to theoretical development, conceptual clarity, and further refinement regarding EA, including what it entails, what it means, and how it is used in relation to other concepts and forms of violence.